2015
DOI: 10.1111/jnc.12984
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mitofusin 2 links beta‐amyloid‐mediated mitochondrial fragmentation and Cdk5‐induced oxidative stress in neuron cells

Abstract: Mitochondrial dysfunction is implicated in age-related degenerative disorders such as Alzheimer's disease (AD). Maintenance of mitochondrial dynamics is essential for regulating mitochondrial function. Ab oligomers (AbOs), the typical cause of AD, lead to mitochondrial dysfunction and neuronal loss. AbOs have been shown to induce mitochondrial fragmentation, and their inhibition suppresses mitochondrial dysfunction and neuronal cell death. Oxidative stress is one of the earliest hallmarks of AD. Cyclin-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 73 publications
5
39
0
2
Order By: Relevance
“…Moreover, an inhibition of Cdk5 activity can save mitochondrial damage and prevent neuronal cell death upstream of mitochondrial dysfunction [128]. Cdk5 may cause oxidative stress by disrupting the antioxidant system such as Prx2 and further trigger mitochondrial fragmentation [125]. Moreover, it is reported that the balance of mitochondrial dynamics is sensitive to oxidative stress [129].…”
Section: Cdk5 Elects Mitochondrial Dysfunctionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, an inhibition of Cdk5 activity can save mitochondrial damage and prevent neuronal cell death upstream of mitochondrial dysfunction [128]. Cdk5 may cause oxidative stress by disrupting the antioxidant system such as Prx2 and further trigger mitochondrial fragmentation [125]. Moreover, it is reported that the balance of mitochondrial dynamics is sensitive to oxidative stress [129].…”
Section: Cdk5 Elects Mitochondrial Dysfunctionmentioning
confidence: 98%
“…A lot of studies have proved that oxidative stress and mitochondrial dysfunction occur in an early stage of AD pathology, which precedes the formation of detectable plaques and tangles [125]. Cdk5 is as a direct participation in oxidative stress and mitochondrial abnormality in neurons as well as the generation of Aβ and glutamate, two key players in AD pathology (Fig.…”
Section: Cdk5 Elects Mitochondrial Dysfunctionmentioning
confidence: 99%
“…4 Deletion and/or inhibition of Mfn1 and Mfn2 results in failure of fusion leading to formation of very small mitochondrial fragments with reduced mass, and decreased transport of mitochondrial component proteins leading to neurodegeneration. 19,[70][71][72][73] Deletion of Mfn1 leads to no change in phenotype up to one year of age, whereas deletion of Mfn2 in a subset of dopaminergic neurons leads to hunched and hypoactive mice by 5 weeks of age. 73 Furthermore, loss of Mfn2 results in mitochondrial fragmentation and severe age-dependent motor deficits that precede the loss of dopaminergic terminals in the striatum.…”
Section: Omm Fusionmentioning
confidence: 99%
“…AS-IV also prevented MPP + -induced mitochondrial fragmentation via MsrA, while knocking down MsrA attenuated this protective effect. This effect may be attributed to the fact that MsrA protects mitofusin from oxidation and maintains normal mitochondrial function (43). Since mitochondria are the primary source of ROS and are a major target of oxidative damage, mitochondrial protein dysfunction likely increases MPP + -induced oxidative damage.…”
Section: Discussionmentioning
confidence: 99%